UPAYA PENINGKATAN HASIL BELAJAR MENGGUNAKAN GROUP INVESTIGATION PADA SISWA KELAS 4 SEKOLAH DASAR - Febditya Aji Wijaya; Mawardi Mawardi; Krisma Widi Wardani (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
ABSTRACTThe purpose of this research is to the improve of learning results of the fourth grade science which is the core and achievement school but have learning result that is still felt less of satisfactory. The types of research which used is Classroom Action Research and it is implemented as much as 2 cycles. The research learning model used in this research is group investigation. Instruments used in this study are formative test sheets, observation sheets, documentation, and interviews. In the implementation of the first cycle, there is a change in the improvement of cognitive learning outcomes after the action in cycle II. By executing the action using group investigation model on science learning, there is improvement of psychomotor learning results through observation of the students’ cooperation. In addition, there is also improvement of affective learning results in the students’ behavior. So, it can be concluded that learning by group investigation model can improve the cognitive, affective, and psychomotor learning results on the teaching and learning of science. Keyword : group investigation, learning results, cognitive, affective, psychomotor. ABSTRAKTujuan dari penelitian ini adalah untuk meningkatkan hasil belajar muatan IPA kelas IV yang merupakan sekolah inti dan berprestasi namun memiliki hasil belajar yang masih dirasa kurang memuaskan. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas dan dilaksanakan sebanyak 2 siklus. Model pembelajaran yang digunakan dalam penelitian ini adalah group investigation. Instrumen yang digunakan dalam penelitian ini adalah lembar tes formatif, lembar observasi, dokumentasi, dan wawancara. Pada pelaksanaan tindakan siklus I terjadi perubahan peningkatan hasil belajar kognitif setelah dilaksanakan tindakan pada siklus II. Dengan dilaksanakan tindakan menggunakan model group investigation pada pembelajaran IPA terjadi peningkatan hasil belajar psikomotor melalui pengamatan kerja sama siswa. Selain itu juga terjadi peningkatan hasil belajar Afektif pada perilaku siswa. Jadi dapat disimpulkan bahwa dengan pembelajaran model group investigation dapat meningkatkan hasil belajar kognitif, afektif maupun psikomotor pada muatan pembelajaran IPA.